The Effects of Physical Exertion According to the Monocarboxylate Transporter 1 (MCT1) on the Speed of Lactic Acid Elimination in Futsal Players - Mustafa Jassim Abd Zaed; Shimal H. Hamad Chomani; Marko Joksimovic (Soshum: Jurnal Sosial dan Humaniora, 2021)
To identify the genetic diversity of futsal players in Al Hilla Sports Club for the season (2020-2021) after they were exposed to physical exertion by testing lactic mlss in the speed of recovery and elimination of lactic acid. The main experiment included two phases. The first is knowledge of the genetic diversity of the players. The first advanced level of this gene reached (5 players), the middle level (4 players), and the low level of the gene (3 players), and the second stage Of the experiment is to measure the searched variable (lactic acid) for all levels of the gene and to detect players who have a rapid elimination of lactic acid products. The experiment lasted for (2 months) and the most important conclusions were the high level of the MCT1 gene, the speed of elimination of lactic acid in the working muscles. There is a discrepancy between the hospitalization and the exercises. It appeared that the players who belong to this level have slow recovery Very compared to other levels, and this indicates that they are tired quickly. The players of this level have the advantage of quickly getting rid of lactic acid and recovering recovery compared to the low level, and they show less fatigue than the low level. The speed of elimination of lactic acid is less than the speed of its production, which facilitates the transfer of lactate from the working muscle to the blood and speed to get rid of it. Increasingly intense physical exertion affects the variation in the MCT1 gene level. The players at the high level of the MCT 1 gene showed an advantage in the speed of elimination of lactic acid production compared to the low and medium levels.